Penerapan Terapi Relaksasi Benson dalam Mengurangi Nyeri Akut pada Pasien Post Apendiktomi: Studi Kasus di RSUD Sidoarjo - Suci Fitria Handayani Harahap; Handono Fakhtur Rohman; Tauriana Tauriana (Universitas Nurul Jadid, 2026)
Appendicitis is a surgical condition caused by inflammation of the appendix. To prevent further complications, an appendectomy, commonly called a surgical removal of the inflamed appendix, is performed. One of the clinical manifestations that appears after surgery is a pain response. Pain is a complex, unique, and individual sensation. To reduce or control this pain, non-pharmacological therapies can be used, one of which is Benson relaxation. The purpose of this study was to determine the effectiveness of Benson relaxation on reducing pain intensity in post-appendectomy patients. This study used a case study method in patients with acute post-appendectomy pain in the Mawar Kuning Ward of Sidoarjo Regional Hospital for 3 days of treatment. This study was limited to patients with post-appendectomy pain who had agreed to undergo Benson relaxation therapy intervention, and Benson therapy intervention was administered before pharmacological therapy. The instrument used to assess the results of the intervention was the Numerical Rating Scale (NRS). The results of the study showed a decrease in pain intensity after administering relaxation therapy to post-appendectomy patients with NRS before the intervention being 6 and after the Benson therapy intervention being 2. Based on the results of this case study, it can be concluded that the application of Benson relaxation is effective in overcoming post-appendectomy wound pain.